Participation of visual association areas in social processing emerges when rTPJ is inhibited - Jorge Hevia-Orozco; Azalea Reyes-Aguilar; Erick H. Pasaye; Fernando A. Barrios (eNeurologicalSci, 2022)
During a social evaluation, the right temporo-parietal junction (rTPJ) plays an important role according to its contribution in making inferences about the mental states of others. However, what is the neural response if rTPJ function is inhibited during a mentalizing task? In this study, participants played the Dictator Game with two confederates: one playing cooperation (C) and other playing non-cooperation (NC) role and then they were scanned during a mentalizing test. However, we inhibited rTPJ using transcranial magnetic stimulation (TMS) after they played the game and before they were scanned. In this test, participants read negative (Neg) or positive (Pos) personal situations and then they watched confederate's pictures. Images from the TMS group were compared against controls with no TMS stimulation. After statistical comparison, we found a significantly higher activity in right and left visual association areas (BA 18) during the NCPos > NCNeg condition in the TMS group compared with the No-TMS group. Same visual association areas have been described before when participants are processing visual emotional information or when making a fast social categorization. This could reflect a neural mechanism of socio - emotional categorization that emerges after rTPJ inhibition.